BRIEF 2 – Comparative analysis of goat farming systems in Nepal and their mitigation potential: Comparing results from Heifer and non-Heifer supported cooperatives - Giles, James; Mwema, Emmanuel; Notenbaert, An Maria Omer; Caulfield, Mark E. (2023)
This brief presents the results of a modelling analysis of goat farming systems from three study sites in Nepal, shedding light on the potential greenhouse gas mitigation potential of improved goat production systems as promoted by Heifer Nepal.